2016
DOI: 10.1177/1741143216653973
|View full text |Cite
|
Sign up to set email alerts
|

Constructing identities

Abstract: This article presents research undertaken with female headteachers in UK primary schools and explores several influential discourses in relation to female headteachers' identities. It considers themes inherent in women's narratives as they reflect upon their professional lives and discusses various identities inhabited by female leaders which emerge from the data. It also explores dominant discourses related to the masculine construction of leadership, women's domestic responsibilities and women as enablers, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
7
0
3
Order By: Relevance
“…Educational leadership research has previously shown a deep connection between women’s identities and their work (e.g. Jones, 2017; Thomson, 2005). Identity is not simply about how leaders see themselves, but also how they are perceived by others – and this may be with or against their wishes (e.g.…”
Section: Identity and Professional Identitymentioning
confidence: 99%
“…Educational leadership research has previously shown a deep connection between women’s identities and their work (e.g. Jones, 2017; Thomson, 2005). Identity is not simply about how leaders see themselves, but also how they are perceived by others – and this may be with or against their wishes (e.g.…”
Section: Identity and Professional Identitymentioning
confidence: 99%
“…Es decir, no son inamovibles, sino que más bien responden a un continuo movimiento en el cual los contextos históricos y culturales juegan un rol fundamental (Dubar, 2002;Crow & Møller, 2017). Por lo tanto, no resulta extraño que la identidad y las características del liderazgo en las mujeres directoras se den con relación a lo masculino (Jones, 2017).…”
Section: Identidad Y Trayectoria De Las Directorasunclassified
“…In this context, it becomes necessary to overcome the notion that good educational administration is a “masculine” enterprise, in which the “hegemonic masculinity” tends to be associated with bureaucratic rationality, which is not always compatible with private life or home administration (Blackmore, 2017). Therefore, it is not surprising that the identity and characteristics of leadership in headmistresses could be molded by the masculine image (Jones, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Within this framework, one of the main motivations to work from María Eliana's life history is that in her role of mother, wife, daughter, partner, teacher, and headmistress, among others, she experienced a series of events that connected her personal life with her professional life. These experiences allow the configuration of her leadership identity based on gender roles (Jones, 2017; Lumby, 2015; Weiner and Burton, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation